Mapping Cognitive Profiles in Dyslexia and Mathematical Disabilities: A Narrative Review of the Cattell-Horn-Carroll (CHC) Model (2015–2025) - Izzatin Nida; Augustina Sulastri; Cicilia Tanti Utami (IJIP : Indonesian Journal of Islamic Psychology, 2026)
Dyslexia and mathematical disabilities (MD) are neurodevelopmental disorders that significantly impact academic achievement and require appropriate identification and intervention. This narrative review synthesizes empirical evidence on the application of the Cattell-Horn-Carroll (CHC) Model in mapping cognitive profiles of both conditions. A literature search was conducted across Scopus, Web of Science, PubMed, PsycINFO, and ERIC databases, focusing on publications from 2010-2025. Nine studies met the inclusion criteria and were analyzed thematically. The available evidence, while limited, suggests differentiable but overlapping patterns: dyslexia is consistently associated with deficits in Auditory Processing (Ga) and Short-Term Memory (Gsm), with relative preservation of Fluid Reasoning (Gf). MD, based on limited direct evidence, appears characterized by deficits in Executive Functions and Visual Processing (Gv), with Gsm emerging as a potential common vulnerability factor. However, contradictory findings exist (e.g., Gv deficits reported in some dyslexia studies), and the MD evidence rests primarily on one study. Critical limitations include a small evidence base with no intervention studies, measurement challenges in CHC subtests, poor ecological validity, and overrepresentation of WEIRD samples. The CHC framework provides a useful structure for understanding cognitive diversity in learning disorders, but the evidence base remains too limited to support strong claims. Rigorous longitudinal research, direct comparisons of both conditions, and intervention trials are urgently needed.